2020
DOI: 10.1364/ao.405980
|View full text |Cite
|
Sign up to set email alerts
|

Influence of thermal blooming on the beam quality of an array of Hermite–Gaussian beams propagating in the atmosphere

Abstract: The influence of thermal blooming on the quality of an array of Hermite–Gaussian (H-G) beams propagating in the atmosphere is studied, where the incoherent combination is considered. An analytical expression of the equivalent distortion parameter of such an array is derived and validated. As the mode order or the inverse radial fill factor of an array of H–G beams increases, the thermal blooming effect weakens, requiring more time to reach steady-state thermal blooming. The focal shift of an array of H-G beams… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…Thermal blooming was shown to become less severe as the spatial coherence of a partially coherent beam array was reduced [22]. Recently, we have also found that thermal blooming weakens as the mode order or the inverse radial fill factor of an array of Hermite-Gaussian beams is increased [23], or as the truncation parameter of a Gaussian (GS) beam is decreased [24]. However, the combined laser beams propagating in the thermal atmosphere are only for one single wavelength, but not considering SBC [21][22][23].…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Thermal blooming was shown to become less severe as the spatial coherence of a partially coherent beam array was reduced [22]. Recently, we have also found that thermal blooming weakens as the mode order or the inverse radial fill factor of an array of Hermite-Gaussian beams is increased [23], or as the truncation parameter of a Gaussian (GS) beam is decreased [24]. However, the combined laser beams propagating in the thermal atmosphere are only for one single wavelength, but not considering SBC [21][22][23].…”
Section: Introductionmentioning
confidence: 93%
“…Recently, we have also found that thermal blooming weakens as the mode order or the inverse radial fill factor of an array of Hermite-Gaussian beams is increased [23], or as the truncation parameter of a Gaussian (GS) beam is decreased [24]. However, the combined laser beams propagating in the thermal atmosphere are only for one single wavelength, but not considering SBC [21][22][23]. As far as we know, the earlier studies do not include any assessment of thermal blooming when an SBC beam propagates in the atmosphere.…”
Section: Introductionmentioning
confidence: 96%
“…Based on the numerical simulation, the scaling laws of beam expansion [11] and phase compensation [12] have been investigated. In recent years, Ji and et al have theoretically studied the thermal blooming effect of laser beams propagating through the atmosphere [13,14] and seawater [15] . Zhang and et al have numerically analyzed the beam deviation induced by thermal blooming effect when high-energy laser propagating upwards in the atmosphere [16] .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, laser array beams have become a hot topic in practical applications owing to the wide potential applications in communication, imaging, power beaming, illumination, and so on. [15][16][17][18][19][20] In last decades, the scintillation, statistics, beam spreading and beam quality of array beams in the atmosphere have been reported. [21][22][23][24][25][26][27][28] On the other hand, it has been shown that partially coherent beams are less sensitive to the effect of turbulence than fully coherent beams.…”
Section: Introductionmentioning
confidence: 99%